OPTIMIZATION OF ISOLATION STRUCTURE OF SMELT FURNACES - J.A. ZINCHENKO (Advanced Engineering Research)
The problem about funding of structure of isolation with greatest stability is considered. In the article, there are results of isolation characteristics of crucible furnaces for smelting of cast iron. Modeling of mix preparing for isolation is carried out and its optimal structure is defined. Recommendations of selection and preparing of structure of isolation with the greatest resistance are given.